Influence of Sexually Transmitted Diseases in Pregnant Adolescents on Preterm Delivery and Chorioamnionitis [5J]. (May 2018) - Fuchs, Esther; Dwiggins, Maggie; Lokken, Erica; Eckert, Linda
Abstract : INTRODUCTION: Adolescents have increased preterm birth (PTB) and sexually transmitted infections (STIs). However, data of the impact of STIs on PTB and other infectious complications is lacking. We examined the prevalence and impact of STIs (Gonorrhea, Chlamydia and Trichomonas) on PTB and chorioamnionitis in pregnant adolescents. METHODS: This retrospective cohort study included patients ⩽19 year old at delivery over a 5-year period in an urban hospital. Each adolescents first singleton pregnancy during the study period was included. Logistic regression was used to estimate odds ratio (OR) and 95% confidence intervals (CI) of the association between STIs and pregnancy outcomes. We controlled for potential confounding factors. Chorioamnionitis was diagnosed clinically and histologically. RESULTS: Of the 975 babies delivered to adolescent mothers, 739 deliveries were included in our final analysis. Overall prevalence of STIs during pregnancy was 16.5% (Chlamydia 13.1%, Trichomonas 3.7% and Gonorrhea 3.1%). Our PTB rate was high, 18.1%, (15.02% when excluding transfers from outside the two closest counties). Chlamydia, Trichomonas and Gonorrhea were not associated with increased PTB. While Gonorrhea and Chlamydia did not increase the odds of chorioamnionitis, infection with Trichomonas was associated with a statistically significant 3-fold increased likelihood, OR 2.95 (95%CI 1.29, 6.75). CONCLUSION: We did not find an association between STI and preterm delivery in adolescent patients who had a high PTB rate, possibly secondary to early detection and treatment. However, Trichomonas markedly increased chorioamnionitis risk, especially diagnosed on pathologic specimens. These data support routine screening of all pregnant teenagers for Trichomonas.